The effect of heat treatment on the properties of the new iron-base alloy - Акимов, Олег Викторович; Нури, Сундус Мохаммед (Eastern-European Journal of Enterprise Technologies, 2015)
The aim of the research was to develop a new austenitic dispersion-hardened corrosion-proof and scaling-resistant iron-base alloy. We have selected and analyzed in detail the chemical composition of the desired alloy, made calculation of the charge and held melting in an induction furnace. We have devised a technology of thermal treatment of the resulting alloy and proved that the best mode is hardening at a temperature of 1180 °C and aging at a temperature of 1000 °C that lasts for 1 hour and is followed by cooling in the air. The more intense dispersion hardening of the alloy results in higher values of its strength and ductility. The study of the scaling resistance shows that it is appropriate to use the alloy at temperatures raised up to 750 °C. The experimental study of corrosion resistance of the alloy shows that the alloy is corrosion-proof and not subject to changes in mass when exposed to a 10% sulfuric acid solution.